BEYOND ACHEBE: FEMINIST VOICES AND GENDER FLUIDITY IN IGBO FOLKLORE AND LITERARY ADAPTATION - Hosamani, Suresh M (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This essay returns to Igbo mythology and literary afterlives in fresh terms with feminist debates and gender fluidity’s theme, diverging from the canonical gravitational pull of Chinua Achebe. While novels by Achebe give critical context for literary inscription of Igbo cosmology, Nigerian women writers and scholars have re-read deities, masquerades, kinship groups, and proverbs since then to emphasize women’s fluidity and agency in gendered roles. Interweaving African feminist hermeneutics specifically nego-feminism (Nnaemeka, 2004) and snail-sense feminism (Adimora-Ezeigbo) with indigenous gender studies (Amadiume, 1987; Nzegwu, 2006), and strategic close readings of Flora Nwapa’s Efuru (1966), Chimamanda Ngozi Adichie’s "The Headstrong Historian" (2009), Akachi Adimora-Ezeigbo’s The Last of the Strong Ones (1996), and Chinelo Okparanta’s Under the Udala Trees (2015), the essay illustrates how recent texts mobilize Igbo mythic figures (Ala, Uhamiri), institutions (umuada, female husbands), and performative actions (agbogho mmuo) to decolonize gender. The essay proposes a triangulated model mythic motif, social institution, and artistic adaptationto map the path of feminist voices reclaiming historical woman-centered power and writing new discourses on sexuality and identity onto the current landscape. The study holds that gender fluidity in Igbo societies occurs less as a borrowing from Western theory than as a refigured reading of practices intrinsic to that culture in which gendered functions were always negotiable, context-dependent, and performative. The conclusion calls for sustained work on Nollywood goddess cinema and digital adaptations as living archives of Igbo feminist futures